Detection and isolation of a new member of Burkholderiaceae-related endofungal bacteria from Saksenaea boninensis sp. nov., a new thermotolerant fungus in Mucorales - Yusuke Takashima; Kohei Yamamoto; Yousuke Degawa; Yong Guo; Tomoyasu Nishizawa; Hiroyuki Ohta; Kazuhiko Narisawa (IMA Fungus)
Abstract Thermotolerance in Mucorales (Mucoromycotina) is one of the factors to be opportunistic pathogens, causing mucormycosis. Among thermotolerant mucoralean fungi, Burkholderiaceae-related endobacteria (BRE) are rarely found and the known range of hosts is limited to Rhizopus spp. The phylogenetic divergence of BRE has recently expanded in other fungal groups such as Mortierellaceae spp. (Mortierellomycotina); however, it remains unexplored in Mucorales. Here, we found a thermotolerant mucoralean fungus obtained from a litter sample collected from Haha-jima Island in the Ogasawara (Bonin) Islands, Japan. The fungus was morphologically, phylogenetically, and physiologically characterized and proposed as a new species, Saksenaea boninensis sp. nov. Besides the fungal taxonomy, we also found the presence of BRE in isolates of this species by diagnostic PCR amplification of the 16S rRNA gene from mycelia, fluorescence microscopic observations, and isolation of the bacterium in pure culture. Phylogenetic analysis of the 16S rRNA gene of BRE revealed that it is distinct from all known BRE. The discovery of a culturable BRE lineage in the genus Saksenaea will add new insight into the evolutional origin of mucoralean fungus-BRE associations and emphasize the need to pay more attention to endofungal bacteria potentially associated with isolates of thermotolerant mucoralean fungi causing mucormycosis.